2017
DOI: 10.1016/j.jpolmod.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The demand for public–private crop insurance and government disaster relief

Abstract: Insurance premium subsidies and disaster relief payments are government actions that can help to smooth farmers' incomes between years. In the EU crop insurance based on public-private partnership is promoted. We present an analysis based on farmers' stated preferences with split data approach of crop insurance and disaster relief provided by the government. Results reveal that farmers' willingness to pay for crop insurance is conditional on the prospect for government disaster relief.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 21 publications
0
26
0
1
Order By: Relevance
“…(3) subsidization of IST complies with WTO green-box requirements; (4) it can also cover systemic risks (specifically price risk) that are not covered by purely commercial insurances thus hampering the principles of risk pooling, (5) it is based on a public-private partnership (e.g., Bardají and Garrido, 2016;El Benni et al, 2016, Mary et al, 2013, Meuwissen et al, 2003, 2008Liesivaara and Myyrä 2016a).…”
Section: Background On the Functioning Of The Ist And Its Impact On Fmentioning
confidence: 99%
“…(3) subsidization of IST complies with WTO green-box requirements; (4) it can also cover systemic risks (specifically price risk) that are not covered by purely commercial insurances thus hampering the principles of risk pooling, (5) it is based on a public-private partnership (e.g., Bardají and Garrido, 2016;El Benni et al, 2016, Mary et al, 2013, Meuwissen et al, 2003, 2008Liesivaara and Myyrä 2016a).…”
Section: Background On the Functioning Of The Ist And Its Impact On Fmentioning
confidence: 99%
“…Thus, the government needs to further expand the category and scope of forestry subsidies [26][27][28]. Some scholars analyzed how to improve the subsidy efficiency of forest insurance and found that a single increase in the proportion of insurance subsidies can indeed enhance the willingness of forest owners to purchase insurance, but it also leads to the poor efficiency of subsidy [29][30][31]. The effective insurance needs, types of disasters, development level of the insurance industry, and dependence on subsidies in different areas vary highly.…”
Section: Introductionmentioning
confidence: 99%
“…Recently there have been some limited efforts to estimate insurance demand using nonmarket valuation methods, such as the contingent valuation method (CVM) or DCEs. Liesivaara and Myyrä (2017) conducted a split sample DCE to include disaster aid as a constant variable in estimating WTP for different attributes of a crop insurance product in Finland. They found that expectations of disaster relief meant farmers would be less worried about crop losses.…”
Section: The Problem Of Insurance Demandmentioning
confidence: 99%
“…The Liesivaara and Myyrä (2017) study evaluates attributes of an insurance product, but the relevance of the insights is largely limited to the EU context. Moreover, the focus has been on interaction with co‐risk mitigation options.…”
Section: The Problem Of Insurance Demandmentioning
confidence: 99%